Treaties requiring Congress approval in Peru - Abugattás, Gattás (2019)
This paper presents the problems regarding the application of articles 56 and 57 of the Political Constitution of Peru, referring to cases in which a treaty requires or not to be approved by the Congress before the President express the consent of the State to be bound by it. Raised the problem, this paper analyzes each case in which the Constitution requires the Congress approval, considering the doctrine, the Peruvian practice on the matter, as well as the rules in force and normative proposals.